2020
DOI: 10.1016/j.bbrep.2020.100822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rosuvastatin on the concentration of each fatty acid in the fraction of free fatty acids and total lipids in human plasma: The role of cholesterol homeostasis

Abstract: Each fatty acid (FA) or class of FAs has a different behavior in the pathologies of atherosclerosis. The aim of this study was to investigate changes in the concentration of each fatty acid in the fraction of free fatty acids (FFAs) and total lipids in human plasma after short-term therapy with rosuvastatin as a cholesterol-lowering statin drug. Six hypercholesterolemic men on a habitual diet were studied in a randomized, double-blind, and crossover process. They received 20 mg rosuvastatin or placebo in rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…We expect that the reduction in the levels of these metabolites is a consequence of rosuvastatin treatment rather than the underlying mechanisms of NAFLD because these lipid metabolites are the sources of hepatic lipid accumulation. Statins inhibit the production of cholesterol, which in turn significantly decreases the level of saturated and monounsaturated FAs in total FAs, and exceptionally, octadecenoic acid (C18:1) and octadecadienoic acid (C18:2) [ 54 ]. Another study showed that strong statins, such as rosuvastatin, decreased the DHA levels, although the mechanism is unknown, suggesting that DHA added to the statin would improve the clinical effects [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the reduction in the levels of these metabolites is a consequence of rosuvastatin treatment rather than the underlying mechanisms of NAFLD because these lipid metabolites are the sources of hepatic lipid accumulation. Statins inhibit the production of cholesterol, which in turn significantly decreases the level of saturated and monounsaturated FAs in total FAs, and exceptionally, octadecenoic acid (C18:1) and octadecadienoic acid (C18:2) [ 54 ]. Another study showed that strong statins, such as rosuvastatin, decreased the DHA levels, although the mechanism is unknown, suggesting that DHA added to the statin would improve the clinical effects [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…127 In vivo, data are currently restricted to plasma fatty acid compositions (which may not reflect hepatic lipid composition); however, these studies found that statins increase the proportion of long-chain PUFAs and decrease the proportion of SFAs and MUFAs. 128,129 Furthermore, statin treatment also led to elevations in the n-6/n-3 PUFA ratio 130 ; however, the physiological role this plays in their mode of action remains unclear. Additional studies are required to determine the impact of statins on hepatic lipid composition.…”
Section: Lipid -Lowering Ag Ents a S A P Otential Pharmacother Apymentioning
confidence: 99%
“…Nevertheless, preclinical research suggests that statins may also alter lipid composition in multiple cell lines including human liver cells 127 . In vivo , data are currently restricted to plasma fatty acid compositions (which may not reflect hepatic lipid composition); however, these studies found that statins increase the proportion of long‐chain PUFAs and decrease the proportion of SFAs and MUFAs 128,129 . Furthermore, statin treatment also led to elevations in the n ‐6/ n ‐3 PUFA ratio 130 ; however, the physiological role this plays in their mode of action remains unclear.…”
Section: Lipid‐lowering Agents As a Potential Pharmacotherapymentioning
confidence: 99%
“…These species vary in the lengths of their carbon chains and their level of saturation. Numerous lines of evidence indicate that high free FA and TG concentrations increase the risks of atherosclerotic cardiovascular disease and mortality ( 4 ). However, in routine clinical laboratory testing, the total serum FA and TG concentrations are typically measured.…”
Section: Introductionmentioning
confidence: 99%